Exogenous Semaphorin 3E treatment protects against chlamydial lung infection in mice - Thomas, Rony; Wang, Shuhe; Rashu, Rasheduzzaman; Peng, Ying; Gounni, Abdelilah S.; Yang, Xi (Frontiers in Immunology, 2022)
Recent studies reported that semaphorins play a significant role in various settings of the immune response. In particular, Semaphorin 3E (Sema3E), a secreted semaphorin protein, is involved in cell proliferation, migration, inflammatory responses, and host defense against infections. However, the therapeutic function of Sema3E in bacterial infection has not been investigated. Our data showed that exogenous Sema3E treatment protects mice from chlamydial infection with lower bacterial burden, reduced body weight loss, and pathological changes in the lungs. Cytokine analysis in the lung and spleen revealed that Sema3E-Fc treated mice, compared to saline-Fc treated mice, show enhanced production of IFN-γ and IL-17, but reduced IL-4 and IL-10 production. Cellular analysis showed that Sema3E treatment leads to enhanced Th1/Th17 response but reduced Treg response in lungs following chlamydial infection. Moreover, Sema3E treatment also enhanced the recruitment of pulmonary dendritic cells, which express higher co-stimulatory but lower inhibitory surface molecules. Taken together, this study demonstrates that Sema3E plays a vital role in protective immunity against chlamydial lung infection, mainly through coordinating functions of T cells and DCs.